ENGLISH PROVERBS WITH PHYTOTHEMATIC HYBRID COMPONENTS: SYNTACTIC ANALYSIS (TAMADDUN NURI JURNALI, 2025)
Proverbs serve as an essential component of linguistic and cultural heritage, encapsulating wisdom, traditions, and values. This study focuses on English proverbs that contain phytothematic hybrid components, i.e., plant-related words of mixed linguistic origins, and analyzes their syntactic structures. The research identifies common syntactic patterns, investigates the role of hybrid phytonyms in meaning construction, and explores their grammatical functions. The findings contribute to a deeper understanding of hybridization in phraseology and its impact on cross-linguistic analysis.